2021
DOI: 10.1155/2021/9090338
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Fetal Weight Estimation by Ultrasonographic Evaluation in a Northeastern Region of India

Abstract: Background and Objectives. Fetal weight evaluation in utero is a significant component in obstetric practices. The present study aims to estimate the fetal weight (EFW) by evaluating two available formulas using ultrasound parameters and comparing them with actual birth weight (ABW) after delivery. The accuracy and efficacy of both EFW formulas in detecting intrauterine growth retardation (IUGR) and macrosomia were also compared in our local sample of the population. Methods. The cross-sectional study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In recent years several EFW prediction models have been developed, but none of these models were practiced in routine clinical applications or recommended according to the current guidelines. Hadlock’s formula is still thus far one of the best-established weight estimation formulas and the one most widely used in everyday routine work, despite recent studies indicating potential ways to decrease MAPE, the especially in macrosomic fetuses and other deviant cases [ 8 , 23 ]. Although, due to the drastic difference in the number of participants, the MAPE in this study was slightly higher than that calculated by Konwar [ 8 ] or Weiss [ 23 ] (5.79% for DNN estimation and 6.46% for Hadlock’s formula), the DNN model still predicted the EFW more accurately compared to the Hadlock’s formula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years several EFW prediction models have been developed, but none of these models were practiced in routine clinical applications or recommended according to the current guidelines. Hadlock’s formula is still thus far one of the best-established weight estimation formulas and the one most widely used in everyday routine work, despite recent studies indicating potential ways to decrease MAPE, the especially in macrosomic fetuses and other deviant cases [ 8 , 23 ]. Although, due to the drastic difference in the number of participants, the MAPE in this study was slightly higher than that calculated by Konwar [ 8 ] or Weiss [ 23 ] (5.79% for DNN estimation and 6.46% for Hadlock’s formula), the DNN model still predicted the EFW more accurately compared to the Hadlock’s formula.…”
Section: Discussionmentioning
confidence: 99%
“…Hadlock’s formula is still thus far one of the best-established weight estimation formulas and the one most widely used in everyday routine work, despite recent studies indicating potential ways to decrease MAPE, the especially in macrosomic fetuses and other deviant cases [ 8 , 23 ]. Although, due to the drastic difference in the number of participants, the MAPE in this study was slightly higher than that calculated by Konwar [ 8 ] or Weiss [ 23 ] (5.79% for DNN estimation and 6.46% for Hadlock’s formula), the DNN model still predicted the EFW more accurately compared to the Hadlock’s formula. Moreover, the frequency of samples with large deviation (> 500 g) was also significantly smaller compared to Hadlock’s formula, indicating that the DNN model can reduce large estimated errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been done for comparing the USG fetal weight with actual birth weight. 11,12,13 A study conducted by Paravathavarthini et al showed that USG was closer to estimating the fetal weight than the actual birth weight. 14 Other studies have also shown that ultrasonographic estimation is more accurate in estimating fetal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous sonographic formulas for determining fetal weight have been developed; however, the accuracy of these formulas varies among research. These disparities may be attributable to variables like differences in research populations, variations in biometric measures used, and inconsistencies in formula creation processes [5,6]. Therefore, a complete analysis of multiple formulas is required to discover the formula that consistently yields the best accurate fetal weight estimations.…”
Section: Introductionmentioning
confidence: 99%